Corn Oil Ketogenic Diet - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The successful substitution of corn oil for MCT oil in 6 children treated with the ketogenic diet for intractable seizures is reported from the Depts of Pediatrics, Neurology and Psychiatry, University of Arkansas for Medical Sciences and Arkansas Children's Hospital, 804 Wolfe St., Little Rock, AR.